Evidence of a humid mid-Holocene in the western part of Chinese Loess Plateau - An, CB; Feng, ZD; Tang, LY (SCIENCE CHINA PRESS, 2003)
Field works show that the wetland/swamp layers were distributed ubiquitously in the western part of the Chinese Loess Plateau. Universality of the wetland/swampy layer and the consistency of the age reveal that the layer was developed under the humid climatic condition. Dated between 9 and 3.8 kaBP, the wetland/swampy layer is full of aquatic mollusks and has the highest tree and shrub pollen, indicating a humid mid-Holocene. Variations of grain size suggest that winter monsoon weakened during 9-3.8 kaBP while climate change to humid and vegetation cover increased from 9 kaBP onward. After 5.9 kaBP, the humidity declined gradually. In 3.8 kaBP, summer monsoon sharply retreated, and the climate changed to dry.